2014
DOI: 10.1001/jama.2014.2138
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Alcohol Screening and Brief Intervention for University Students

Abstract: anzctr.org.au Identifier: ACTRN12610000279022.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
1
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 38 publications
5
57
1
13
Order By: Relevance
“…Lastly, this review synthesizes literature that was published by October of 2011, consistent with the evidence available when e-SBI was presented to the Task Force. It is possible that the magnitude of the findings would differ with the inclusion of more recent studies; however, effect estimates from more recent studies 78,79 are consistent with those found in this review, making it unlikely that their inclusion would substantively alter the results reported in this review.…”
Section: Discussionsupporting
confidence: 53%
“…Lastly, this review synthesizes literature that was published by October of 2011, consistent with the evidence available when e-SBI was presented to the Task Force. It is possible that the magnitude of the findings would differ with the inclusion of more recent studies; however, effect estimates from more recent studies 78,79 are consistent with those found in this review, making it unlikely that their inclusion would substantively alter the results reported in this review.…”
Section: Discussionsupporting
confidence: 53%
“…19 Therefore, a campus-based screening and counseling is highly favorable to be routinely employed among incoming and current college students. 20,21 In executing this intervention, a more focused attention needs to be paid to identify high risk groups. In this study we have found that males are consistently being alcohol consumer more than females.…”
Section: Discussionmentioning
confidence: 99%
“…There is also some evidence that being self-administered, online screening is likely to generate more honest reporting of risky alcohol use, in comparison with a face-to-face interview [27, 28]. The AUDIT-C has been used to screen for eligibility in two trials of web-based alcohol screening and brief intervention delivered to students in New Zealand (≥4 for men and women) [29, 30] and two trials of facilitated access to an online intervention delivered in primary care in Italy and Spain (≥5 for men and ≥4 women) [31, 32]. These trials did not validate the AUDIT-C for use online, and were not conducted in general population samples.…”
Section: Introductionmentioning
confidence: 99%